A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

GLUT1-mediated glucose import in B cells is critical for anaplerotic balance and humoral immunity - Bierling, Theresa; Gumann, Amelie; Ottmann, Shannon; Schulz, Sebastian; Weckwerth, Leonie; Thomas, Jana; Geßner, Arne; Wichert, Magdalena; Kuwert, Frederic; Rost, Franziska; Hauke, Manuela; Freudenreich, Tatjana; et al. (Cell Reports, 2024)
Glucose uptake increases during B cell activation and antibody-secreting cell (ASC) differentiation, but conflicting findings prevent a clear metabolic profile at different stages of B cell activation. Deletion of the glucose transporter type 1 (GLUT1) gene in mature B cells (GLUT1-cKO) results in normal B cell development, but it reduces germinal center B cells and ASCs. GLUT1-cKO mice show decreased antigen-specific antibody titers after vaccination. In vitro, GLUT1-deficient B cells show impaired activation, whereas established plasmablasts abolish glycolysis, relying on mitochondrial activity and fatty acids. Transcriptomics and metabolomics reveal an altered anaplerotic balance in GLUT1-deficient ASCs. Despite attempts to compensate for glucose deprivation by increasing mitochondrial mass and gene expression associated with glycolysis, the tricarboxylic acid cycle, and hexosamine synthesis, GLUT1-deficient ASCs lack the metabolites for energy production and mitochondrial respiration, limiting protein synthesis. We identify GLUT1 as a critical metabolic player defining the germinal center response and humoral immunity.
CRIS-Team Scopus Importer:2024-02-23
Keywords: adaptive immune response; antibody-secreting cell; CP: Immunology; CP: Metabolism; glucose transporter type 1; GLUT1; glycolysis; metabolism; mitochondrial respiration; plasma cell; plasmablast

Humoral and Cellular Immune Responses to SARS–CoV-2 Infection and Vaccination in Autoimmune Disease Patients With B Cell Depletion - Simon, David; Tascilar, Koray; Schmidt, Katja; Manger, Bernhard; Weckwerth, Leonie; Sokolova, Maria; Bucci, Laura; Fagni, Filippo; Manger, Karin; Schuch, Florian; Ronneberger, Monika; Hueber, Axel; et al. (Arthritis and Rheumatology, 2021)
Objective: B cell depletion is an established therapeutic principle in a wide range of autoimmune diseases. However, B cells are also critical for inducing protective immunity after infection and vaccination. We undertook this study to assess humoral and cellular immune responses after infection with or vaccination against SARS–CoV-2 in patients with B cell depletion and controls who are B cell–competent. Methods: Antibody responses (tested using enzyme-linked immunosorbent assay) and T cell responses (tested using interferon-γ enzyme-linked immunospot assay) against the SARS–CoV-2 spike S1 and nucleocapsid proteins were assessed in a limited number of previously infected (n = 6) and vaccinated (n = 8) autoimmune disease patients with B cell depletion, as well as previously infected (n = 30) and vaccinated (n = 30) healthy controls. Results: As expected, B cell and T cell responses to the nucleocapsid protein were observed only after infection, while respective responses to SARS–CoV-2 spike S1 were found after both infection and vaccination. A SARS–CoV-2 antibody response was observed in all vaccinated controls (30 of 30 [100%]) but in none of the vaccinated patients with B cell depletion (0 of 8). In contrast, after SARS–CoV-2 infection, both the patients with B cell depletion (spike S1, 5 of 6 [83%]; nucleocapsid, 3 of 6 [50%]) and healthy controls (spike S1, 28 of 30 [93%]; nucleocapsid, 28 of 30 [93%]) developed antibodies. T cell responses against the spike S1 and nucleocapsid proteins were found in both infected and vaccinated patients with B cell depletion and in the controls. Conclusion: These data show that B cell depletion completely blocks humoral but not T cell SARS–CoV-2 vaccination response. Furthermore, limited humoral immune responses are found after SARS–CoV-2 infection in patients with B cell depletion.
CRIS-Team Scopus Importer:2021-12-03

Metabolic profiling of single cells by exploiting NADH and FAD fluorescence via flow cytometry - Abir, Ariful Haque; Weckwerth, Leonie; Wilhelm, Artur; Thomas, Jana; Reichardt, Clara; Munoz, Luis Enrique; Völkl, Simon; Appelt, Uwe; Mroz, Markus; Niesner, Raluca; Hauser, Anja; Fischer, Rebecca Sophie; et al. (Molecular Metabolism, 2024)
Objective: The metabolism of different cells within the same microenvironment can differ and dictate physiological or pathological adaptions. Current single-cell analysis methods of metabolism are not label-free. Methods: The study introduces a label-free, live-cell analysis method assessing endogenous fluorescence of NAD(P)H and FAD in surface-stained cells by flow cytometry. Results: OxPhos inhibition, mitochondrial uncoupling, glucose exposure, genetic inactivation of glucose uptake and mitochondrial respiration alter the optical redox ratios of FAD and NAD(P)H as measured by flow cytometry. Those alterations correlate strongly with measurements obtained by extracellular flux analysis. Consequently, metabolically distinct live B-cell populations can be resolved, showing that human memory B-cells from peripheral blood exhibit a higher glycolytic flexibility than naïve B cells. Moreover, the comparison of blood-derived B- and T-lymphocytes from healthy donors and rheumatoid arthritis patients unleashes rheumatoid arthritis-associated metabolic traits in human naïve and memory B-lymphocytes. Conclusions: Taken together, these data show that the optical redox ratio can depict metabolic differences in distinct cell populations by flow cytometry.
CRIS-Team Scopus Importer:2024-07-19
Keywords: FAD; Flow cytometry; Fluorescence; Metabolism; NADH; Real-time

Metabolic regulation of plasma cell generation in germinal centers through EFhd2 - Weckwerth, Leonie; Gottwald, A.; Mielenz, Dirk (EUROPEAN JOURNAL OF IMMUNOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-27

Mitochondrial respiration in B lymphocytes is essential for humoral immunity by controlling the flux of the TCA cycle - Urbanczyk, Sophia; Baris, Olivier R.; Hofmann, Jörg; Taudte, Verena; Guegen, Naïg; Golombek, Florian; Castiglione, Kathrin; Meng, Xianyi; Bozec, Aline; Thomas, Jana; Weckwerth, Leonie; Mougiakakos, Dimitrios; et al. (Cell Reports, 2022)
To elucidate the function of oxidative phosphorylation (OxPhos) during B cell differentiation, we employ CD23Cre-driven expression of the dominant-negative K320E mutant of the mitochondrial helicase Twinkle (DNT). DNT-expression depletes mitochondrial DNA during B cell maturation, reduces the abundance of respiratory chain protein subunits encoded by mitochondrial DNA, and, consequently, respiratory chain super-complexes in activated B cells. Whereas B cell development in DNT mice is normal, B cell proliferation, germinal centers, class switch to IgG, plasma cell maturation, and T cell-dependent as well as T cell-independent humoral immunity are diminished. DNT expression dampens OxPhos but increases glycolysis in lipopolysaccharide and B cell receptor-activated cells. Lipopolysaccharide-activated DNT-B cells exhibit altered metabolites of glycolysis, the pentose phosphate pathway, and the tricarboxylic acid cycle and a lower amount of phosphatidic acid. Consequently, mTORC1 activity and BLIMP1 induction are curtailed, whereas HIF1α is stabilized. Hence, mitochondrial DNA controls the metabolism of activated B cells via OxPhos to foster humoral immunity.
CRIS-Team Scopus Importer:2022-06-17
Keywords: B lymphocyte; class switch recombination; CP: Immunology; germinal center; HIF1; hypoxia inducible factor 1; mammalian target of Rapamycin; mitochondrial DNA; mitochondrial respiration; mTOR; oxidative phosphorylation; phosphatidic acid; plasma cell; TCA cycle